2016
DOI: 10.4049/jimmunol.1600159
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish IRF1, IRF3, and IRF7 Differentially Regulate IFNΦ1 and IFNΦ3 Expression through Assembly of Homo- or Heteroprotein Complexes

Abstract: In mammals, IFN regulatory factor (IRF)1, IRF3, and IRF7 are three critical transcription factors that are pivotal for cooperative regulation of the type I IFN response. In this study, we explored the relative contribution of zebrafish (Danio rerio) IRF1 (DrIRF1), IRF3 (DrIRF3), and IRF7 (DrIRF7) (DrIRF1/3/7) to zebrafish IFNΦ1 (DrIFNΦ1) and IFNΦ3 (DrIFNΦ3) (DrIFNΦ1/3) activation. Following spring viremia of carp virus infection, DrIFNΦ1/3 and DrIRF1/3/7 transcripts are significantly induced in zebrafish tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 57 publications
3
41
0
Order By: Relevance
“…infected cells. In the zebrafish ZFL cell line, SVCV rapidly activates ifnphi1 and ifnphi3 expression from 12 to 24 hpi (Feng, 2016) although times of SVCV infection later than 24 hpi were not examined in that study.…”
Section: Discussionmentioning
confidence: 99%
“…infected cells. In the zebrafish ZFL cell line, SVCV rapidly activates ifnphi1 and ifnphi3 expression from 12 to 24 hpi (Feng, 2016) although times of SVCV infection later than 24 hpi were not examined in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Fish IRF7 is a true ortholog of mammalian IRF7. A recent study showed that fish IRF7 is also involved in regulating IFN expression and undergoes phosphorylation (33). Nevertheless, little is known about the regulation mechanisms of IRF7 activity in fish.…”
Section: Discussionmentioning
confidence: 99%
“…A transgenic reporter zebrafish identified hepatocytes and neutrophils as the two main cell types expressing IFNφ1 (group I) in larvae upon alphavirus infection [34]; a more recent IFNφ3 (group II) reporter line suggests a completely non-overlapping pattern of expression, including fibroblasts (Briolat, Lutfalla, and Levraud, unpublished result). The contributions of IRF1/3/7 to the induction of IFNφ1 and IFNφ3 have been studied in vitro, providing first insights for anatomical complementarity of different IFN [35], as detailed below. In grass carp ( Ctenopharyngodon idella ), four type I IFN were also identified, CiIFN1 and four with two cysteines (group I) and CiIFN2 and three with four cysteines (group II); group II IFNs were transiently induced in gills and spleen by GCRV infection in adult fish, while CiIFN1 was constitutively expressed in gills, spleen, liver and gut, and CiIFN4 was never detectable in any condition tested [36].…”
Section: Differential Expression and Functional Properties Of Fishmentioning
confidence: 99%
“…When the reporters were activated by an “upstream” trigger (such as overexpression of TBK-1), expression of a dominant negative version of either IRF3 or IRF7 (but not IRF1) inhibited luciferase production [40,42]. Further biochemical studies indicated that these three IRFs can either homo- or hetero-dimerize and suggested that IRF3 facilitates the binding of IRF1 or IRF7 to the promoters [35]. In summary, the zebrafish IFNφ1 promoter is predominantly controlled by IRF3, and IFNφ3 by IRF7, like IFNβ and IFNα, respectively.…”
Section: Differential Expression and Functional Properties Of Fishmentioning
confidence: 99%